Screening for Early Emerging Mental Experiences (SEE ME): A Model to Improve Early Detection of Psychosis in Integrated Primary Care - Woodberry, Kristen A.; Johnson, Kelsey A.; Shrier, Lydia A. (Frontiers in Pediatrics, 2022)
Early intervention in serious mental health conditions relies on the accurate identification of adolescents and young adults at high risk or with very recent onset of psychosis. Current early detection strategies have had limited success, identifying only a fraction of these individuals within the recommended 3- to 6-month window. Broader public health strategies such as population screening are hampered by low base rates and poor self-report screen specificity. Screening for Early Emerging Mental Experiences (SEE ME) is a three-stage “SCREEN—TRIAGE—ENGAGE” model for the early detection of psychosis in integrated primary care adolescent and young adult patients during the period of peak onset. It builds on the KNOW THE SIGNS—FIND THE WORDS—MAKE THE CONNECTION framework outlined on psychosisscreening.org and developed with input from community collaborators. Systematic screening aims to expand the reach of early detection and reduce reliance on provider knowledge. Triage and engagement by trained mental health clinicians aims to improve the specificity of screen responses, enhance engagement in appropriate care, and reduce provider burden. Leveraging the low stigma of primary care, its reach to non-help-seeking adolescents and young adults, and the mental health training of clinicians within integrated care practices, SEE ME has potential to improve the benefit/risk ratio of early detection of psychosis by improving both the sensitivity and specificity of screening and clinical response. We review the rationale and design of this promising model.